Production of bioethanol from oil palm industrial solid waste by single-step bioconversion process - Alam, Md. Zahangir; Kabbashi, Nassereldeen; Tompang, Mohamad Fahrurrazi (2006)
The bioethanol production was conducted by utilizing palm oil solid residues, empty fruit bunches (EFB) with the treatment of mixed culture of fungi and yeast in solid state bioconversion process. The compatibility of several fungal and yeast, were tested as to develop direct solid state bioconversion using the potential mixed culture. The mixed culture of fungi (Trichoderma harzianum) and yeast (Saccharomyces cerevisiae) has found to be the most potential as they produced higher ethanol among the other combination of mixed culture in liquid-broth fermentation for compatibility test. The optimization of process condition was done with varied level of moisture content, pH, inoculum size, concentration of co-substrate and mineral solution by using the central composite design (CCD). The optimum process conditions with maximum ethanol production (14.1%) were: moisture of 60%, pH of 7, inoculum size of 4%, co-substrate concentration of 2% and minerals concentration of 2%. The result indicated that pH, co-substrate and minerals concentration were highly significant (p<0.001)followed by moisture content (p<0.005) and inoculum size (p<0.005). The coefficient of determination (R2) was 99.6% which satisfied the adjustment of experimental data in the model. A validation experiment was been carried out to evaluate the process conditions obtained from model.